PENGARUH KELELAHAN OTOT TERHADAP KETELITIAN KERJA (THE INFLUENCE OF MUSCLE FATIGUE ON WORK CAREFULNESS) - Tecky Indriana (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Human life cannot be separated from activities. Human body has the ability to adapt and it has resistance to fatigue, but this capability has its restriction. So, whenever an activity is done on and on for a long time, then fatigue will occur. Fatigue can influence work productivity, one of which is work carefulness. In dentistry, work carefulness is required to get maximum result. The aim of this research is to know the influence of fatigue on students’ work carefulness of Faculty of Dentistry, University of Jember. The subjects of the research were 30 students of Faculty of Dentistry, University of Jember, male and female at the age of between 20 and 30 who do not suffer from color blind. The subjects were instructed to arrange beads with correct color order (green, white, blue, purple, orange, pink, and red) for 10 minutes. The bead arrangement that the subjects made were then counted based on the correct color order and their work carefulness was counted. Then, the research subjects were asked to step up and down the step-test bench once in every three seconds for two minutes to produce fatigue. Then the research subjects were instructed to arrange beads again and their work carefulness was counted. The result of the research was analyzed by using t-test, and it showed that there was a difference (p<0,05) on the level of work carefulness before and after the occurrence of fatigue that is, work carefulness decreases when fatigue occurs